The structure and evolution of production, employment and human capital in Portugal - Lopes, João Carlos (2014)
The main purpose of this paper is to analyse the structure and evolution of production, employment and human capital in Portugal, using an inter-industry approach. A descriptive analysis of the sector composition of gross output, value added and employment is made, followed by a quantification of changes in relative labour productivity and primary input content of final demand components. Next, the evolution of employment multipliers is quantified, as well as the structure of labour force qualifications by sector. Although remarkable improvements have been achieved in the past, the low educational levels of its workers, on average, remains one the main vulnerabilities of Portugal in the global and knowledge economy of our days. In this context, the main contribution of the paper is the quantification of human capital requirements of final demand changes by component. Using an input-output approach combining sector productivities and labour qualifications, output multipliers and final demand structure, it is possible to quantify the growth in employment by level of qualification resulting from a unitary growth of private and public consumption, investment and exports. This exercise is made for 1995 and 2008, using input-output domestic flow tables from INE and DPP and employment qualifications from Quadros de Pessoal database.